EFFICACY OF TRAINING WITH GADGETS ON SHOULDER AND LEG EXPLOSIVE POWERS OF MEN TENNIS PLAYERS - P. Vijayakumar; E. Amudhan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this study was to investigate the efficacy of training with gadgets on selected motor fitness variables in male tennis players. Thirty male tennis players from Sri Ramakrishna Mission Vidyalaya Maruthi College of Physical Education and Ramakrishna Mission Vivekananda Educational and Research Institute, Periyanaickenpalayam, Coimbatore, Tamil Nadu, were randomly assigned to two equal groups: the Training with Gadgets Group (TWGG) and the Control Group (CG), with fifteen participants in each group. The experimental group participated in a 12-week training programme incorporating gadgets, while the control group continued their regular routine without any specialized intervention. The selected dependent variables for the study were Shoulder Explosive Power and Leg Explosive Power. The independent variable was the training with gadgets. A paired t-test was used to analyze the pre- and post-test results, with a significance level set at 0.05. The results indicated a significant improvement in both Shoulder Explosive Power and Leg Explosive Power for the experimental group, suggesting that training with gadgets effectively enhanced these motor fitness variables in male tennis players